Tekun Dalam Pengharapan Makna (Ibrani 10:23) - Hot Nome; Abad Jaya Zega (Student Research Journal, 2023)
"Perseverance is a profound and crucial trait when facing life's challenges. This article explores the concept of perseverance in the context of expectations, delving into how it can be the key to success in various aspects of life. Expectation is a psychological component that drives individuals to achieve their goals. Perseverance, on the other hand, is the ability to stay focused and determined in the face of obstacles, even in the presence of uncertainty."